A Criminalização da Juventude Pobre na Paraíba: Reflexões acerca das Mudanças e Permanências - Amorim, Tâmara Ramalho de Sousa (2013)
The youth category can be seen as a social condition and can be considered in its plural - youths. This dissertation will address to a specific youth: the poor youth, which historically has been subjected to disciplinary measures, for example, through institutionalization. In Paraíba, among the institutions created to intervene with these young, the Pindobal institution and the Adolescent Educational Center (Centro Educacional do Adolescente CEA) stand out. The first one was created in 1929, and the second one in 1990. Throughout history, these institutions were responsible for receiving abandoned young or those who have committed some infraction. Given the above, the general objective of this dissertation is to analyze the criminalization of the poor youth and the subjectivation processes through the institutionalization history of punitive practices in Paraíba, from Pindobal to CEA. And the specific objectives are identify the profile of former inmates and students; to tell the story of the Pindobal institution; tell the story of the CEA institution; characterize the forms of punitive practices applied to poor youth, from Pindobal to CEA; identify the discourse of psychology on the institutionalization of punitive practices in the context of the CEA institution; analyze the subjectivation of former inmates and students from the institutionalization process. The theoretical framework follows the post-structuralist perspective of Foucault, as from the categories Institutionalization, Criminalization, Punitive Practices and Subjectivation. Regarding the method, the locus of the research consisted of historical institutes, newspaper archives, Councils of law and Pindobal and CEA institutions. Nineteen participants were interviewed (the number was defined by the technique of data saturation), divided into 05 groups: former Pindobal inmates, former Pindobal professionals, students from CEA, CEA professionals and oral history informants. The techniques and instruments used were document research and semi-structured interviews. For the latter, different interview guides were used for participants, considering the group of former inmates and students, and the group of professionals. The interviews were recorded, transcribed and submitted to Critical Discourse Analysis, as from the following categories: Who speaks? From where does he or she speak? What effect of meaning does it generate? Which discourses appear? From which event is the story retold? Which history does the orality reveal? The results showed that the profile of former inmates and students consists of young people from the lower classes, ie, poor youth. They also indicated that: punitive practices applied to poor young from Pindobal to CEA were, in general, physical punishment and imprisonment; the discourse of psychology in the context of CEA was configured to be an individualizing discourse; and the subjectivation of former inmates and students can be analyzed, among other aspects, through the history of institutionalization that they present, and through the internalization of discourses. The general set of findings in this research revealed the history of poor, abandoned, orphaned, "delinquent" young. These are subjects who engender themselves from practices that are settled down in the institution. And the story of these young people is the story of the criminalization through the way of those who lived it.